An analysis of virtual triage utilization by pregnant women prior to and during the COVID-19 pandemic - Jaszczak, Jakub; Gellert, George A.; Gellert, Gabriel L.; Suwińska, Aleksandra (Frontiers in Global Women's Health, 2024)
ObjectiveThis analysis describes the use patterns of web-based virtual triage (VT) by pregnant patients before and during the first two years of the COVID-19 pandemic, and how the pandemic influenced frequency of VT use, nature of symptoms reported, and the associated implications for maternal healthcare delivery.MethodsAn online survey of 36,910 patients who reported pregnancy was completed between January 1, 2019 and June 30, 2022. The data were segmented into six month periods to allow comparative analyses of usage frequency and changes in initial complaints over the study period, with particular emphasis on the early months of the COVID-19 pandemic. Descriptive statistics and trend analyses were used to identify significant shifts in symptom reporting and user demographics.ResultsA marked increase in the utilization of VT by pregnant women during the pandemic occurred. The percentage of pregnant users grew from 0.32% in the first half of 2019 to 0.85% in late 2021, with the greatest rise (213%) in the first six months of 2020. The most common symptoms reported were abdominal pain, headache, nausea, back pain, fatigue and cough. Pre-pandemic, VT use focused on prospective mothers learning about the potential causes of typical symptoms occurring during pregnancy, but during the pandemic there was a substantial increase in reporting symptoms associated with acute respiratory infections such as cough, nasal congestion, and dyspnea.ConclusionsThe COVID-19 pandemic significantly influenced the use of VT by pregnant women, with a shift towards addressing concerns related to respiratory symptoms and potential COVID-19 exposure. These findings underline the significant role of digital health tools in maintaining access to health information during times of crisis and highlight the evolving needs of pregnant patients in such settings.